6th Aeroacoustics Conference 1980
DOI: 10.2514/6.1980-1025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of several inflow control devices for flight simulation of fan tone noise using a JT15D-1 engine

Abstract: As part of a program to enable accurate simulation of in-flight fan tone noise during ground static tests, four devices intended to reduce inflow disturbances and turbulence were tested with a JT15D-1 turbofan engine. These inflow control devices (ICD's) consisted of honeycomb/ r, screen structures mounted over the engine inlet. The ICD's ranged from 1.6 to 4 fan diameters in size, and differed in shape and fabrication method. All the ICD's significantly reduced the BPF tone in the farfield directivity pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…3 and discussed in the Introduction. Other circumferential modes, such as m=\6 and 10 are possible, due to rotor interaction with higher harmonics of strut-induced distortion.…”
Section: Far Field a Coustic Effectsmentioning
confidence: 98%
See 3 more Smart Citations
“…3 and discussed in the Introduction. Other circumferential modes, such as m=\6 and 10 are possible, due to rotor interaction with higher harmonics of strut-induced distortion.…”
Section: Far Field a Coustic Effectsmentioning
confidence: 98%
“…This mode was shown to exist in the inlet duct of a JT15D engine when the results from two pressure sensors located in the duct so as to allow spining mode identification by signal phase relationship were used. 3 However, it was not possible to alter the support struts in the engine to establish the behavior of this apparent noise source.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…3 showed that propagating modes at BPFF could be producedby rotor interaction with distortions from ICU ribs and from engine struts aft of the fan in the bypass flow duct. On the basis of those results and as illustrated in Fig.…”
Section: Cut-off Speedsmentioning
confidence: 99%